Monitoring urban physical growth in tsunami-affected areas: a case study of Banda Aceh City, Indonesia - Amri, Ikhwan (Springer Science and Business Media Deutschland GmbH, 2022)
Building back better-based urban planning is an integral part of efforts to increase urban resilience. Therefore, urban physical growth needs to be monitored to prevent built-up areas from expanding into hazard zones. This study analyzed the dynamics of urban physical growth and its driving forces in tsunami-affected areas of Banda Aceh after the 2004 tsunami. Built-up areas were extracted from Landsat images. The annual growth rate equation was used to estimate the growth characteristics in the tsunami-affected and safe areas. In-depth interviews and extensive literature reviews were also conducted to identify the determinant factors of urban redevelopment in tsunami-affected areas. Results showed that the annual growth rate was high in the areas during the disaster recovery period (2005–2009). Nevertheless, urban physical growth dominated in the safe areas during 2009–2019. The study also identified several driving forces of urban physical growth in the hazard zones: (1) population growth, (2) spatial planning, (3) distance to old city center, (4) land ownership and prices, and (5) socio-economic factors. This study provided new insights for urban planners to reduce disaster risk in urban areas. © 2021, The Author(s), under exclusive licence to Springer Nature B.V. part of Springer Nature.